Assessment of Trisama, an ayurvedic formulation on intestinal transit time in swiss albino mice - Patel, Amit G. (Ayu, 2018)
BACKGROUND: Trisama is an Ayurvedic formulation that can be prescribed for wide range of disorders, especially abdominal disorders such as indigestion, constipation and flatulence. Trisama is prepared by mixing an equal quantity of powder of Shunthi (Zingiber officinale Linn.), Haritaki (Terminalia chebula Retz.) and Guduchi (Tinospora cordifolia [Willd.] Miers.). As a single ingredient, Haritaki is an alternative to prokinetic drugs, Guduchi for intestinal motility and Shunthi for digestion-related problems. MATERIALS AND METHODS: The present study aims to evaluate the effect of Trisama dosage forms on intestinal motility by adopting kaolin expulsion test in Swiss albino mice. Trisama powder (0.65 and 1.3 g/kg) and Trisama decoction (12.48 ml/kg) were administered and intestinal transit time of kaolin and latency of onset of kaolin expulsion in fecal matter was assessed. RESULTS: Both the dosage forms of Trisama shortened the intestinal transit time of kaolin. However, the observed effects were statistically significant in Trisama powder at higher dose and Trisama decoction in comparison to control group. The behaviors of mice and consistency of fecal pellet were almost the same as observed in normal control group. CONCLUSION: From the present study, it is concluded that Trisama has significant intestinal motility-enhancing property in mice which may be useful in gastric problems without affecting the general physiology.